O-015 Contrast transit time changes on digital subtraction angiography following pipeline flow diversion. (23rd July 2017) - Brunozzi, D; Shakur, S; Charbel, F; Alaraj, A
Abstract : Introduction: Pipeline embolization devices (PED) are used for endovascular treatment of cerebral aneurysms but can be associated with delayed ipsilateral intraparenchymal hemorrhage (DIPH). Changes in intracranial hemodynamics after PED are poorly understood. Here, we assess hemodynamic changes after PED in patients with and without DIPH. Methods: Records of patients with distal internal carotid artery (ICA) aneurysms treated with PED at our institution between 2012–2017 were retrospectively reviewed. Regions of interest were selected proximally to PED over the cavernous ICA and distally over the middle cerebral artery (MCA), and then transit times were determined using syngo iFlow software (Siemens). Ratio of MCA to ICA transit time was compared before and after treatment using Wilcoxon matched-pairs signed-ranks test. Ratios were also compared between patients with and without DIPH using 2-sample Wilcoxon rank-sum test. Results: 53 patients were included (mean age 56 years). Ratio of MCA to ICA transit time decreased significantly after PED deployment (1.13 vs. 1.23, p<0.01, figure 1A). Ratio in DIPH + group (n=4) was significantly lower (1.00 vs. 1.13, p=0.01, Fig B) and decreased significantly more (21% vs. 4.4%, p=0.02) compared to DIPH – group (n=49). The ratio tended to be higher in larger aneurysms at baseline (p=0.07) but not after PED treatment (p=0.15). Conclusion: Ratio of MCA to ICA transit time decreases more in patients with DIPH following PED treatment. These contrast transit time changes can be detected in real-time in the neuroangiography suite. Disclosures: D. Brunozzi: None. S. Shakur: None. F. Charbel: 2; C; Transonic. 4; C; Ownership VasSol Inc. A. Alaraj: 1; C; NIH. 2; C; Cordis-Codman.